Examining the association between peer support and English enjoyment in Chinese university students: the mediating role of regulatory emotional self-efficacy - Pan, Xiaoquan; Yuan, Zihan (Frontiers in Psychology, 2023)
As positive psychology is imported into second language acquisition, we witness the increasing interest in the research of English enjoyment. Therefore, investigating the antecedents of English enjoyment is of paramount importance. Although internal and external factors have been scrutinized by researchers, scarce studies have explored the effect of peer support and regulatory emotional self-efficacy on English enjoyment. Thus, this study was designed to further clarify the association between these two constructs and English enjoyment. A questionnaire involving the three variables of peer support, English enjoyment and regulatory emotional self-efficacy was administered to 324 non-English major undergraduate students at a comprehensive university in Eastern China. Correlation analysis and mediation effect tests indicated that peer support and regulatory emotional self-efficacy positively predicted English enjoyment, and regulatory emotional self-efficacy played a mediating role between peer support and English enjoyment. This study highlighted the significance of peer support and positive emotions in second language learning and extended our understanding on enhancing students' learning enjoyment through teachers' positive intervention to facilitate peer support and emotional regulation self-efficacy.